COVID-19 and (Im)mobilities in West Africa - Breuer, Andreas; Doevenspeck, Martin; Donko, Kamal; Ouedraogo, Soumaila (University of Bayreuth African Studies Working Papers, 2021)
This study examines recent developments of mobility patterns in West Africa within the context of the ongoing COVID-19 pandemic. A broad understanding of mobilities is applied to account for mobilities of people, goods and capital likewise. The aim is to track changes in mobility patterns caused by the pandemic and by institutional responses to the latter. The study may herein serve to encourage more in depth and comprehensive studies of the new (im)mobilities and the regimes that shape them. Embedding the subject of mobility changes into the political-economic framework of the networks of global capitalism and taking a perspective on the formative regimes, we develop first suppositions on how to apply the concept of (im)mobility regimes to assess the newly manifested (im)mobilisations. To shed light on the bigger picture of recent developments in Western Africa, this study tackles a wide range of mobility-related topics. At first, the epidemiological situation as well as the local testing regimes are analysed in order to assess the extent to which the pandemic is scientifically captured in Western Africa in contrast to other regions. By then providing a systematic outline of the lockdown policies of the individual ECOWAS member states, a first approach to the formative regimes can be given. The manifest new (im)mobilities of people are then evaluated with a focus on public transport, migratory movements and public air travel. Thereafter, the (im)mobilities of goods are discussed with a special focus on maritime freight mobilities. Finally, (im)mobilities of capital are dealt with in order to address changes and constants in the context of COVID-19, for example in the realm of remittances. Overall, this provides a first basis for a multi-dimensional understanding of the emerging phenomena in the ECOWAS region.
Keywords: Mobility; Immobility; (im)mobility regimes; West Africa; COVID-19; pandemic; Goods; Capital flows; Migration; Refugees; Google COVID-19 Community Mobility Reports; Mobility pattern; Lockdown; Air traffic; Aviation; Border; Travel; PHSM; ECOWAS; Shipping; Container; Freight; Commodities; FDI; Remittances; Ratings; Trade; Testing; Infections; public transport; Ports; Cluster of Excellence Africa Multiple; African Studies